PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BLACKBERRY (Studi Kasus pada Mahasiswa S1 FISIP Universitas Diponegoro Semarang) - Maria Dewi Ratnasari; Agus Hermani Seno; Sari Listyorini (Universitas Diponegoro, 2014)
This research aims to know the influence of the brand image and product quality of the purchasing decisions and POLITICAL SCIENCE undergraduates Blackberry UNDIP Semarang. This research type is explanatory research. The population in this research is the undergraduate student and POLITICAL SCIENCE UNDIP Semarang. The number of samples in the study amounted to 100 students. Sampling techniques in the study using a purposive sampling. Engineering data collection using the questionnaire and the study of the literature. The scale of measurement using Likert scale. On data analysis using simple linear regression test and test multiple regression with application programs SPSS 16.0. Results of the study suggested that there is a positive influence and strong brand image among variables of a purchase Blackberry, indicated by the coefficient of the correlation coefficients and regression 1,246 0,718 and contributing 51,67%.In addition there is a very strong and positive influence of the variable quality of products towards purchasing decision Blackberry, indicated by the coefficient of the correlation coefficients and regression 0,302 0,943 and contributes 89,0. While together the brand image and product quality has a positive influence on the buying decision of linear regression coefficients shown duality of the brand image and product quality 0,292 0,072, besides its influence is very strong, brand image and product quality together affects the purchasing decisions of the correlation coefficient is shown by the 0,944 and contributing 89.1.